The impact of menstrual cycle phase on athletes` performance: A narrative review - Carmichael, M. A.; Thomson, R. L.; Moran, L. J.; Wycherley, T. P. (International Journal of Environmental Research and Public Health, 2021)
The effect of the menstrual cycle on physical performance is being increasingly recognised as a key consideration for women`s sport and a critical field for further research. This narrative review explores the findings of studies investigating the effects of menstrual cycle phase on perceived and objectively measured performance in an athletic population. Studies examining perceived performance consistently report that female athletes identify their performance to be relatively worse during the early follicular and late luteal phases. Studies examining objective performance (using anaerobic, aerobic or strength-related tests) do not report clear, consistent effects of the impact of menstrual cycle phase on physical performance. Overall sport performance can be influenced by both perceived and physical factors. Hence, to optimise performance and management of eumenorrheic female athletes, there is a need for further research to quantify the impact of menstrual cycle phase on perceived and physical performance outcomes and to identify factors affecting variability in objective performance outcomes between studies.